Crisis in Dutch Universities of Applied Sciences - De Wit, Hans (International Higher Education, 2012)
Universities of Applied Sciences in The Netherlands are facing severe criticism from media and politicians about their performance. The main issues are the quality of their degrees, including accusations of diploma fraud, high dropout rates and poor graduation rates. This negative perception of the current performance of Dutch universities of applied sciences should be understood in the context of reform of Dutch higher education and of the demands of the global knowledge society. In comparison with the universities of applied sciences in other countries, which earlier and more gradually have adapted to the requirements from the professional field, Dutch universities of applied sciences face a difficult time. The danger might be that the distance to the research universities and to the universities of applied sciences in other countries is increasing rather than decreasing, and this might impact negatively the still strong reputation of several of its programs. The sector cannot ignore that there is a serious quality issue, which is difficult to solve due to years of ignoring to address the changes that the knowledge economy requires.